Zdrowie w perspektywie historycznej i antropologicznej = Health from historical and anthropological perspective - Malinowski, Andrzej (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Anthropology as a science provides basic knowledge on interpopulation, interspecies, intrapopulation, dimorphic and ontogenetic variability. The paper presents the notion of health and illness from the historical perspective (from the Palaeolithic through Ancient Greece and Rome to contemporary times). The author describes mutual theoretical and practical relations of anthropology with health, and indicates health measures used to evaluate the health status of a population (both positive and negative). In promoting health by doctors, PE teachers and valeologists, he emphasizes indispensable knowledge regarding such notions as a norm of reaction, adaptive norm, adaptability, adjustment (including health, vigour of life, extensivity) or homeostasis and homeorhesis.
Keywords: zdrowie; choroba; antropologia; waleologia; badania; health; illness; anthropology; valeology; researches